Instrumental variables, local instrumental variables and control functions - Jean-Paul Florens; James Heckman; Costas Meghir; Edward Vytlacil (Centre for Microdata Methods and Practice (cemmap), 2002)
We consider the identification of the average treatment effect in models with continuous endogenous variables whose impact is heterogeneous. We derive a testable restriction that allows us to assess the degree of unobserved heterogeneity. Our analysis uses assumptions relating to the Local Instrumental Variables (LIV) approach and the control function approach.
Keywords: 330; Statistischer Test; Instrumentalvariablen-Schätzmethode